The overcoat : Shinel - Bykov, Rolan, 1929-1998; Gogol, Nikolai Vasilevich, 1809-1852; Batalov, Alekseĭ Vladimirovich (Video Russia., 1985)
The story of a clerk whose new overcoat changes his destiny.